2006
DOI: 10.1002/bit.20840
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine‐based “Activatable Pro‐Tag”: Enzyme‐catalyzed protein capture and release

Abstract: Fusion tags are widely used in the recovery and purification of recombinant proteins. We have investigated the capture and release of two fusion proteins from cell extracts using the aminopolysaccharide chitosan. We have fused to green fluorescent protein (GFP) and to S-ribosylhomocysteinase (LuxS) a "pro-tag" consisting of five tyrosine residues that are "activated" by tyrosinase-catalyzed conversion into reactive oquinones. The o-quinones react with the amino groups of chitosan, resulting in the covalent con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 33 publications
2
57
0
Order By: Relevance
“…This agrees with previously reported results (Chen et al, 2003a;Lewandowski et al, 2006) which examined GFP binding to chitosan in solution. Electrodeposited chitosan may have structural and chemical properties that are distinctly different than soluble chitosan, particularly in that the chitosan experiences a high pH for a short time during the electrodeposition.…”
Section: Results and Discussion Enzymatic Activation And Assembly Of supporting
confidence: 94%
See 3 more Smart Citations
“…This agrees with previously reported results (Chen et al, 2003a;Lewandowski et al, 2006) which examined GFP binding to chitosan in solution. Electrodeposited chitosan may have structural and chemical properties that are distinctly different than soluble chitosan, particularly in that the chitosan experiences a high pH for a short time during the electrodeposition.…”
Section: Results and Discussion Enzymatic Activation And Assembly Of supporting
confidence: 94%
“…Finally, we expect the vast majority of GFP molecules to be specifically oriented through the C-terminal pro-tags as they assemble onto the scaffold surface, as we previously demonstrated that GFP preferentially grafts to chitosan through the pro-tag versus native tyrosines by a ratio of over 4:1; that is, over 80% of binding is through the pro-tag (Lewandowski et al, 2006). This enables orientational control and contrasts considerably with an additional previous approach, where the protein was covalently linked through its native amines to a glutaraldehyde-activated chitosan film surface and thus in no particular orientation (Yi et al, 2005a).…”
Section: Results and Discussion Enzymatic Activation And Assembly Of mentioning
confidence: 81%
See 2 more Smart Citations
“…In the second method, the Pfs predominately conjugates to the surface of the electrodeposited chitosan film, as Pfs is presented after chitosan deposition, and as diffusion of Pfs into the film is presumably limited due to steric hindrance effects. Additionally, Pfs preferentially conjugates to chitosan film through its C-terminal protag vs. its native tyrosines, 34 indicating that Pfs is preferentially oriented through the pro-tag with respect to the film surface. Thus, the Pfs assembled by the second method is expected to be more accessible for antibody binding, which is consistent with the strong fluorescence intensity of Figure 2b.…”
Section: Discussionmentioning
confidence: 99%